Dynamics of CO2 Density‐Driven Flow in Carbonate Aquifers: Effects of Dispersion and Geochemistry. Issue 4 (6th April 2021) - Erfani, Hamidreza; Babaei, Masoud; Niasar, Vahid
Abstract: The dissolution of carbon‐dioxide (CO2 ) in deep saline aquifers is an important trapping mechanism in carbon storage. This process is triggered by unstable high‐density CO2 front, which later promotes density‐driven mixing, hydrodynamic dispersion of CO2, and favors the long‐term sequestration. In many former studies, effects of hydrodynamic dispersion and multispecies geochemical reactions have been ignored. This work elaborates the impacts of these simplifications on the dynamics of convective mixing by numerical simulations. Geochemical effects were studied by the implementation of rock‐fluid and fluid‐fluid interactions for a typical carbonate aquifer. Results show that accounting for the hydrodynamic dispersion decreases the convection onset time and increases the CO2 dissolution flux, which is more significant in larger dispersivities and Rayleigh numbers. Results indicate that carbonate geochemical reactions intense the long‐term overall efficiency of the process, while decrease the total amount of sequestered carbon in the diffusion‐dominated period. Results also reinforce the importance of realistic geochemical representation and importance of spatial and temporal dependence of the reactions pathway, subsequent to the finger development for more detailed simulation of the CO2 storage process. Plain Language Summary: Geological carbon storage is one of the technologies envisaged to play a critical role in decarbonization and achieving the net‐zero carbon emission. It is estimated that 17% of the whole decarbonization by 2050 will be achieved by carbon storage. Based on a modeling study, we demonstrate the role of natural geochemistry of the subsurface is important in the dissolution of carbon in brine and its long‐term performance. Key Points: Effect of hydrodynamic dispersion is studied on the dynamics of CO2 convection Chemical reactions have nonmonotonic effects on carbon storage before and after convection onset The importance of realistic geochemical modeling and different reaction pathways subsequent to plume propagation is shown